The functional role of the medial motion area V6 - Pitzalis, Sabrina; Fattori, Patrizia; Galletti, Claudio (Frontiers in Behavioral Neuroscience, 2013)
In macaque, several visual areas are devoted to analyze motion in the visual field, and V6 is one of these areas. In macaque, area V6 occupies the ventral part of the anterior bank of the parieto-occipital sulcus (POS), is retinotopically-organized and contains a point-to-point representation of the retinal surface. V6 is a motion sensitive area that largely represents the peripheral part of the visual field and whose cells are very sensitive to translational motion. Based on the fact that macaque V6 contains many real-motion cells, it has been suggested that V6 is involved in object-motion recognition. Recently, area V6 has been recognized also in the human brain by neuroimaging and electrophysiological methods. Like macaque V6, human V6 is located in the POs, is retinotopically organized, and represents the entire contralateral hemifield up to the far periphery. Human V6, like macaque V6, is a motion area that responds to unidirectional motion. It has a strong preference for coherent motion and a recent combined VEPs/fMRI work has shown that area V6 is even one of the most early stations coding the motion coherence. Human V6 is highly sensitive to flow field and is also able to distinguish between different 3D flow fields being selective to translational egomotion. This suggests that this area processes visual egomotion signals to extract information about the relative distance of objects, likely in order to act on them, or to avoid them. The view that V6 is involved in the estimation of egomotion has been tested also in other recent fMRI studies. Thus, taken together, human and macaque data suggest that V6 is involved in both object and self-motion recognition. Specifically, V6 could be involved in 'subtracting out' self motion signals across the whole visual field and in providing information about moving objects, particularly during self-motion in a complex and dynamically unstable environment.